MANAJEMEN PELAYANAN MUSIK GEREJA STUDI DESKRIPTIF GEREJA SIDANG JEMAAT ALLAH (GSJA) SUNSET KUPANG DALAM MASA PANDEMI CORONA - Jeny Tamonob (Institut Agama Kristen Negeri Kupang, 2022)
This study aims to describe and examine church music services during the Covid-19 pandemic and to find out how the church music service management was used by the worship team of GSJA Sunset Church Kupang during the Covid- 19 pandemic. The research method used is descriptive qualitative research. Data collection techniques were carried out using interview methods, direct observation and document recording in the research area. Qualitative data analysis techniques, namely data reduction, data presentation and verification using general management function theory and church music ministry management theory to analyze the data in the study. Given that because there was during the Covid-19 pandemic, the church music ministry carried out its ministry role only on Sunday services which were conducted online. Team Worship at GSJA Sunset Church Kupang has managed to carry out its management function well, but there are still some obstacles that make the church music service less than optimal, including: it takes longer to get good music and vocals, mistakes occur when taking music and vocals, lack of adequate facilities to carry out the recording process and the occurrence of differences of opinion between fellow serving teams. After explaining the management functions that occurred in the worship team during the pandemic, namely the function of planning, organizing, directing, coordinating and monitoring, according to the writer of the worship team at GSJA Sunset Church Kupang, it has been successfully implemented even though GSJA Sunset Church Kupang did not learn about management science in theory. In line with the results of the above research, the writer can suggest that it would be better if every worship team should be able to train their ability in music and be able to build cooperation between fellow service teams and can learn from other churches in terms of music management or human resource management. exist in the church with the aim of improving the quality of the church.